2004
DOI: 10.1097/00003246-200412001-00332
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Consumption, Pco2 Gradients and Regional Blood Flow Distribution in an Alternative Model of Intestinal Autotransplantation

Abstract: Introduction: Although the necessity of small bowel (SB) vs gastric placement of FTs remains controversial, many prefer to use SB feeds. However, challenges in getting FTs into the SB may limit delivery of early enteral nutrition. We compared placement of FTs using the "corkscrew" technique described by Zaloga (CHEST, 1991) and the new Gabriel® magnetized FT with those placed by the patient's bedside nurse. Hypothesis: FTs inserted by individuals trained and coached in specific methods would be more successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 0 publications
3
8
0
Order By: Relevance
“…On the other hand, we found a good correlation between mesenteric venous-arterial pCO 2 and intestinal oxygen extraction in both experimental models, in line with earlier studies [5,13,20]. However, it should be noted that a better correlation of these parameters (D mv-a pCO 2 and O 2 ER intest) occurs below the critical oxygen delivery as observed in the SMVO group.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, we found a good correlation between mesenteric venous-arterial pCO 2 and intestinal oxygen extraction in both experimental models, in line with earlier studies [5,13,20]. However, it should be noted that a better correlation of these parameters (D mv-a pCO 2 and O 2 ER intest) occurs below the critical oxygen delivery as observed in the SMVO group.…”
Section: Discussionsupporting
confidence: 92%
“…DO 2 was not achieved during this period. These results are in line with other studies that showed that intestinal oxygen consumption is independent of blood flow until a critical reduction in regional blood flow is reached, usually less than 50%-60% of the baseline measurements [18][19][20].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the monoclonal antibodies targeting the molecular markers on human lymphocytes, e.g., alemtuzumab (anti-CD52 antibody) and thymoglobulin, cannot be used as induction agents in animals. Despite these limitations, however, animals are still useful for building a surgical model of small bowel transplantation [14][15][16][17][18]22].…”
Section: Discussionmentioning
confidence: 99%